HU-USM STUDENT FORUM DISCUSSES GLOBALISATION AND SUSTAINABILITY ISSUES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
HIROSHIMA, JAPAN, 11 December 2015 14 students of Universiti Sains Malaysia (USM) and 14 students from Hiroshima University (HU), Japan attended the HUUSM Student Forum 2015 to discuss globalisation and sustainability issues for five days, from 7 to 11 December 2015.